2008
DOI: 10.1111/j.1475-6773.2008.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and Long‐Term Mortality after an Acute Illness for Elderly Whites and Blacks

Abstract: Racial disparities in health are more likely to be generated in the posthospital phase of the process of care delivery rather than during the hospital stay. The slower rate of increase in relative mortality among black VA patients suggests an integrated health care delivery system like the VA may attenuate racial disparities in health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 30 publications
0
51
1
Order By: Relevance
“…Level 1 demographics were most commonly evaluated, and of the studies that did multivariate analyses, increased mortality was observed for older 8,16,20,[24][25][26] and male 8,20,24 patients. The pattern for race was mixed with one study showing decreased mortality 27 for blacks and two showing no statistical difference. 27,28 Hispanics 25 and Asians 25 had lower mortality.…”
Section: Social Factors Associated With Mortality In Pneumoniamentioning
confidence: 96%
See 2 more Smart Citations
“…Level 1 demographics were most commonly evaluated, and of the studies that did multivariate analyses, increased mortality was observed for older 8,16,20,[24][25][26] and male 8,20,24 patients. The pattern for race was mixed with one study showing decreased mortality 27 for blacks and two showing no statistical difference. 27,28 Hispanics 25 and Asians 25 had lower mortality.…”
Section: Social Factors Associated With Mortality In Pneumoniamentioning
confidence: 96%
“…The pattern for race was mixed with one study showing decreased mortality 27 for blacks and two showing no statistical difference. 27,28 Hispanics 25 and Asians 25 had lower mortality. Level 2 and 3 social factors were examined less frequently.…”
Section: Social Factors Associated With Mortality In Pneumoniamentioning
confidence: 96%
See 1 more Smart Citation
“…differences in short-term survival may also reflect a "survivor effect" in which blacks who survive to age 65 may represent a healthier cohort of patients than white patients of the same age. [13][14][15] It is also unknown whether black patients with larger MIs may be more likely to die before reaching the hospital; therefore, those blacks who are admitted may have less severe disease than whites. In addition to age and sex, there are likely additional unmeasured differences between these groups that confer a protective benefit toward black patients that we have not fully captured or adjusted for.…”
Section: Short-term Mortalitymentioning
confidence: 99%
“…Several prior analyses have found similar results of a short-term survival advantage among blacks compared with whites for cardiac and noncardiac conditions. [13][14][15]24,25 One possibility for these findings in black patients may be the higher prevalence of type 2 or secondary MIs seen in the setting of renal failure or hypertensive disease. These MIs are caused by increased oxygen demand or decreased oxygen supply rather than acute plaque rupture 26 and are often associated with smaller infarct size and less myocardial damage as evidenced by lower troponin elevations.…”
mentioning
confidence: 97%